2011
DOI: 10.1093/brain/awr199
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble tumour necrosis factor is therapeutic in experimental autoimmune encephalomyelitis and promotes axon preservation and remyelination

Abstract: Tumour necrosis factor is linked to the pathophysiology of various neurodegenerative disorders including multiple sclerosis. Tumour necrosis factor exists in two biologically active forms, soluble and transmembrane. Here we show that selective inhibition of soluble tumour necrosis factor is therapeutic in experimental autoimmune encephalomyelitis. Treatment with XPro1595, a selective soluble tumour necrosis factor blocker, improves the clinical outcome, whereas non-selective inhibition of both forms of tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
201
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(213 citation statements)
references
References 61 publications
12
201
0
Order By: Relevance
“…For example, EAEinduced changes in expression of H2-Ab1, Mbp, Nrg1, Snap25, and Grin1 were prevented in the presymptomatic phase of disease by XPro1595 administration. We (37) and other investigators (53) showed that XPro1595 protects mice against clinical MOGinduced EAE when administered in prophylactic and therapeutic protocols. There, protection was not paralleled by a reduction in inflammatory lesions in the spinal cord, but with reduced overall neuroinflammation and preservation of myelin and neuron integrity during full-blown disease.…”
Section: Discussionmentioning
confidence: 80%
“…For example, EAEinduced changes in expression of H2-Ab1, Mbp, Nrg1, Snap25, and Grin1 were prevented in the presymptomatic phase of disease by XPro1595 administration. We (37) and other investigators (53) showed that XPro1595 protects mice against clinical MOGinduced EAE when administered in prophylactic and therapeutic protocols. There, protection was not paralleled by a reduction in inflammatory lesions in the spinal cord, but with reduced overall neuroinflammation and preservation of myelin and neuron integrity during full-blown disease.…”
Section: Discussionmentioning
confidence: 80%
“…In support of this finding, we here provide compelling evidence in an in vivo model of NMDAinduced acute neuronal lesions that abrogation of complete TNF signaling by blocking both TNFRs is not protective, because mounting of a neuroprotective TNFR2-dependent response is prevented. However, preclinical studies in the experimental autoimmune encephalomyelitis (EAE) model (36)(37)(38) or a mouse model of spinal cord injury (39) revealed that selective neutralization of sTNF/TNFR1 signaling is neuroprotective. Of note, in the EAE model, systemic application of TNFR1-blocking antibodies proved to be therapeutically effective (40).…”
Section: Resultsmentioning
confidence: 99%
“…The increased production of proinflammatory cytokines and infiltration of peripheral immune cells into the central nervous system (CNS) are closely associated with neuronal damage in the spinal cord and many brain regions (6)(7)(8)(9)(10). Elevation of several cytokines such as TNF-α and IFN-γ precedes infiltration of peripheral immune cells and could have a significant impact on neuronal function (11)(12)(13)(14)(15)(16)(17)(18)(19), potentially contributing to early sensory and cognitive impairments.…”
mentioning
confidence: 99%
“…A dominant negative TNF inhibitor, XPro1595, blocks the effects of solTNF to selectively decrease the activation of TNFR1 (35,36). Recently, decreased activation of TNFR1 via XPro1595 has been shown to promote axonal integrity and improve clinical outcome of mice with EAE (10).…”
mentioning
confidence: 99%